IMPROVING STUDENT LEARNING OUTCOMES IN PROCEDURE TEXT WRITING MATERIALS THROUGH THE USE OF MULTIMEDIA - Rahmawati Rahmawati; Sitti Rabiah; Andi Puspitasari (Citra Dharma Cindekia, 2022)
The purpose of this study was to find out the results of improving students' reading skills by implementing reading booths at the MA Islamic Boarding School Mizanul ulum Sanrobone. The design of this research is classroom action research. Classroom action research has four procedures in its implementation, namely planning, action implementation. Observation and reflection. The subjects in this study were students of class XI IPS MA at the Mizanul'ulum Sanrobone Islamic Boarding School. Learning activities with procedural text material using multimedia learning models were welcomed by teachers and students. The increase that shows students in class XI IPA 2 in each cycle is the success of researchers in applying the multimedia learning model in increasing student interest in learning with procedural text material in class XI IPA 2 students at SMA Negeri 1 Takalar. The average score for pre-cycle speaking development was 57.77, increasing by 5.28 points to 63.05 after the first cycle of action was held. At the end of the second cycle of action, the average score obtained by students reached 80.33. This shows an increase of 17.27 points.